Resistance of foodborne pathogen coliphages to thermal and physicochemical treatments applied in food manufacture - Tomat, David Damian (2015)
In the present work, six bacteriophages (DT1 to DT6) with lytic activity against one enteropathogenic (EPEC) and two Shiga-toxigenic (STEC) Escherichia coli strains were tested for their resistance to physicochemical conditions/treatments applied on food industry, either under conditions found in the food matrix such as different pH, cation concentrations, and water activity (Aw), and/or found during the manufacture process, namely thermal treatments at 63, 72 and 90 °C. Furthermore, phage viability was assessed at refrigeration and abusive temperature, different salt concentrations, and relevant pH values found in meat and dairy products. Phages were completely inactivated at 90 °C, though DT2 and DT6 showed higher thermal resistance since phage particles were detected after 2 min. In addition, Tris-magnesium gelatin buffer seems to be the most protective suspension medium with increasing temperature. Phage viability was slightly or moderately affected at 63 °C and 72 °C, respectively. All the cations evaluated showed no influence on phage viability, and the same was true for the low Aw values assayed, namely 9.5 and 9.0. The six phages tolerated pH treatments well, being more resistant to alkaline conditions (up to pH 11). Results showed that the activity of the phages evaluated was only partially affected - at the lowest temperature (regarding control temperature; 37 °C), with increasing Na+ concentration, and at the lowest pH value (regarding control pH; 7.5) - and most tested conditions allow phages to multiply in the three pathogenic Escherichia coli strains evaluated. These results help to improve both selection of phages and time point, e.g. on a HACCP system, where phages may be applied on food during their manufacture in order to maximize phage effectiveness against pathogenic STEC and EPEC strains in the food chain. Therefore, the phages evaluated in this study could be used on several food matrices since they are viable and active in a wide range of environmental food conditions.